Development of a Design Tool for Rapid Gravity Media Filtration in Water Treatment - Ingle, Laura (Department of Civil Engineering, 2023)
Filtration is the most commonly used water treatment process (Gray, 2010) and can be found at every water treatment plant in South Africa (Van Duuren, F. A., South Africa Water Research Commission., 1997). Therefore, the design, evaluation and improvement of filtration systems is (and should be) ongoing. Currently there is seemingly a lack of consolidated information to enable filter designers to quickly and easily design and evaluate various filtration systems, as it is not always possible to conduct thorough pilot-testing at design stage. This study addresses the development of a detailed filter design tool that enhances the plant-wide water treatment design tool that incorporates a high-level filter design spreadsheet previously developed by Morrison (2019). This study presents guidelines to filter designers for the whole filtration process based on a literature review that consolidates key aspects and design parameters such as media selection and characterisation, filtration rate selection, operation and control, backwash rates, head losses, filter components, configuration and geometry. These parameters are documented in this dissertation and incorporated into the design tool, thus ensuring that the designer obtains relevant insights to the various parameters and their effects. This study focuses on rapid filtration as it is the most common granular filtration technology (Crittenden et al., 2012). The design tool is developed in Microsoft Excel and is intended for exclusive use by the author's employer at the time of submission. The tool itself provides a mechanism for the designer to easily review the effects of various interlinked parameters in developing and refining a filter solution. The outputs of such a tool can be utilised further in plant-wide treatment models.